inggis - Hidayatulloh, Rifqi; Atmaja, Baluh Medyabrata; Hutabarat , Amelia Lulu Rosalin; Lestari, Wenni Meika; Agasi , Satri Yusasra; Ali , Muhammad Irvan (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2024)
This research evaluates the phenotypic characteristics of male Peranakan Ongole (PO) cattle in Napis Village, Tambakrejo District, Bojonegoro Regency, East Java. The research method used is a case study through observation, photography, and direct measurement. The location and research sample were determined through purposive sampling based on the characteristics of cattle according to SNI 2020 PO cattle. The evaluation encompassed 109 male PO cattle, categorized by age, ranging from PI0 to PI8. The research results show that the qualitative characteristics of male PO cattle, including dominant white body color, black eyelashes, black muzzle, horns, dewlap, and hump, are in accordance with the SNI 7651.5:2020 standard. In addition, morphometric characteristics such as body weight, withers height, body length, chest circumference, hip height, hip width, and chest depth significantly increased (P<0.05) with the age of the cattle. This data shows the optimal growth pattern of male PO cattle, which can be used as a reference in genetic selection programs and the development of superior-quality seeds. This research emphasizes the strategic potential of Napis Village as a source of high-quality PO cattle seeds in Indonesia.